The Role of the 14–20 Domain of the Islet Amyloid Polypeptide in Amyloid Formation. (10th June 2008) - Gilead, Sharon; Gazit, Ehud
Abstract : The molecular mechanism of amyloid formation by the islet amyloid polypeptide (IAPP) has been intensively studied since its identification in the late 1980s. The IAPP(20–29) region is considered to be the central amyloidogenic module of the polypeptide. This assumption is mainly based on the amyloidogenic properties of the region and on the large sequence diversity within this region between the human and mouse IAPP, as the mouse IAPP does not form amyloids. A few years ago, another region within IAPP was identified that seems to be at least as important as IAPP(20–29) in facilitation of molecular recognition that leads to amyloid formation. Here, we reinforce our and others' previous findings by analyzing supporting evidence from the recent literature. Moreover, we provide new proofs to our hypothesis by comparing between the amyloidogenic properties of the two regions derived from the IAPP of cats, which is also known to form amyloid fibrils.